New species of Anthurium sect. Calomystrium (Araceae) from Colombia - Sierra-Giraldo, Julio Andrés; Orozco-A, Jairo Andrés; Trujillo-Trujillo, Edwin; Castaño-Rubiano, Natalia (Phytotaxa, 2022)
A new species of Anthurium sect. Calomystrium from Colombia is described and illustrated. It is distributed in the east of the Caldas department, in the forests surrounding Florencia (Samaná), elevation between 1300–1700 m in clearings and forest edges. The new species is compared with the most closely related taxa (A. mariae y A. palacioanum) and comments about its geographical distribution, phenology and conservation status (Data Deficient) were made.